Severe Convective Storms and Tornadoes Observations and Dynamics - Bluestein, Howard B.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book is a focussed, comprehensive reference on recent research on severe convective storms and tornadoes. It will contain many illustrations of severe storm phenomena from mobile Doppler radars, operational Doppler radars, photographs and numerical simulations.
Basic equations -- Observing systems and the analysis and interpretation of their data -- Ordinary-cell convective storms -- Supercells -- Mesoscale convective systems (MCSs) -- Tornadoes -- Forecasting -- Areas of future research -- Theory.
Keywords: Geography; Remote sensing; Ecology; Earth Sciences; Atmospheric Sciences; Meteorology; Remote Sensing/Photogrammetry.; Geoecology/Natural Processes